The effect of madrasah principals' leadership style and work environment on the teachers performance - Sriwijayanti Sriwijayanti; Happy Fitria; Achmad Wahidy (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
The goal of this research is to determine the influence of the Madrasah Principal Leadership Style and Work Environment on the performance of Sekayu District State MT teachers. The analysis was carried out in the district of Negeri Sekayu MTs. This type of study is quantitative in descriptive terms. 84 respondents with data collection techniques in the form of a questionnaire were the sample in the analysis (questionnaire). Documentation and. The findings show that: 1) there is an effect on teacher performance of the principal's leadership style, 2) there is an impact of the working environment on teacher performance, 3) there is an influence on teacher performance between the principal's leadership style and the working environment together.